Walking behavior of pedestrian social groups on stairs: A field study. (August 2019) - Fu, Libi; Cao, Shuchao; Shi, Yongqian; Chen, Siyuan; Yang, Panyun; Fang, Jie
Highlights: A field study was conducted to explore group walking behavior on stairs. Average distances for groups of different sizes are relatively stable. Groups can form a flexible structure even under the effect of stair step constraint. Members belonging to the same group seek to move at similar speed and offset angles. Pedestrian characteristics can impact on group walking speed and dissimilarity. Abstract: There is growing consensus that most pedestrians in a crowd walk in groups, and these groups have an influence on crowd dynamics whenever under natural or emergency situations. Despite this fact, however, empirical data on group walking behavior on stairs are limited. This paper aims to explore how group members interact with each other and how groups organize on stairs. In order to achieve these, a field study was conducted on stairs in a campus of a university. A total of 105 pedestrian groups descending the stairs were selected as observation subjects. After obtaining their trajectories by the optimal flow algorithm, interpersonal distances and angles between group members, average speed, space-time diagrams offset angles and walking dissimilarity on stairs were calculated and analyzed. Results demonstrate that average distances for groups of different sizes are relatively stable. Groups with different sizes on stairs can form different walking patterns. Members belonging to the same group always seek to move at similar speed and offset angles, and can adjust their motion during the descending process, in order to ensure comfortable group walking and coherence. It is discovered that group size has a significant negative effect on average group speed. Gender and social relationships have little influence on group walking speed and dissimilarity values, except in dyads. These findings have implications for group walking modelling and safe pedestrian facility design.